A MCDM approach for selection of microgrid configuration for rural water pumping system. (March 2023) - Mosetlhe, Thapelo; Babatunde, Olubayo; Yusuff, Adedayo; Ayodele, Temitope; Ogunjuyigbe, Ayodeji
Abstract: This paper presents a framework for the selection of microgrid configuration for water pumping applications in a rural area. The approach adopted is based on multi-criteria decision making. Four criteria, namely, (1) net-present cost, (2) cost of energy, (3) fuel cost, and (4) complexity of the system are used for making the selection. Weights are assigned to the criteria in the order of their importance and TOPSIS and VIKOR methods are used to determine the ranking of the alternatives. The results show the consistency of both methods in ranking the same alternative as the best. Both methods identified the scheme comprising PV–Battery as the best alternative with a closeness coefficient being closer to 1. However, the ranking of the second and fourth alternatives differed for both methods.